Kepemilikan Publik, Tipe Industri Dan Pengungkapan Lingkungan: Studi Komparatif Indonesia Dan Singapura - Fitri Aryanti; Y Anni Aryani (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2020)
This study examines the differences in the level of environmental disclosure of companies in Indonesia and Singapore, and test the influence of public ownership and industry types on environmental disclosures. We use public ownership and industry type as independent variables, and use company age, firm size, debt to equity and profitability as control variables. Measuring the level of environmental disclosure using the GRI-G4 index,the population of this research is the company that issued a sustainability report and is listed on the Indonesia Stock Exchange (IDX) and the Singapore Stock Exchange (SGX). By using purposive sampling method, the research sample used was 103 companies from Singapore and 42 companies from Indonesia. Test analysis proves that there are differences in the level of environmental disclosures in Indonesia and Singapore. From the results of multiple linear regression tests it can be concluded that public ownership does not have a positive effect on environmental disclosure, but the type of industry, and the size of the company has a significant positive effect on environmental disclosure.